The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40064-016-3593-3
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of medicine-related publications on poverty (2005–2015)

Abstract: BackgroundPoverty is a global problem. The war against poverty requires not only financial support, but also poverty-related research to pinpoint areas of high need of intervention. In line with international efforts to fight poverty and negative consequences, we carried out this study to give a bibliometric overview of medicine-related literature on poverty. Such a s study is an indicator of the extent of interaction of various international key players on the war against poverty-related health problems.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 114 publications
(113 reference statements)
1
12
0
1
Order By: Relevance
“…This is the first study reporting and evaluating global trends related to paraquat intoxication research by using bibliometric technique. The major limitations were similar to those identified from previous similar bibliometric studies . The most important limitation lies in the fact that that the analysis of paraquat intoxication‐related publications in the current study cannot be considered to represent the whole global research output in this field, since the data in this study was only collected from Scopus database.…”
Section: Discussionmentioning
confidence: 70%
“…This is the first study reporting and evaluating global trends related to paraquat intoxication research by using bibliometric technique. The major limitations were similar to those identified from previous similar bibliometric studies . The most important limitation lies in the fact that that the analysis of paraquat intoxication‐related publications in the current study cannot be considered to represent the whole global research output in this field, since the data in this study was only collected from Scopus database.…”
Section: Discussionmentioning
confidence: 70%
“…The geographical distribution of publications on HHR was nearly global but with variations in size of research output across the world. Furthermore, geographical distribution was extensively more spread than that obtained for publications in other fields such as poverty or mobile health or global emerging pathogens [ 15 , 21 , 30 ]. The current study indicated that despite the USA was leading in this field; other non-American, non-European countries such as Brazil, India, and South Africa made noticeable contributions.…”
Section: Discussionmentioning
confidence: 99%
“…In bibliometric studies, a large database is used to retrieve relevant documents for subsequent analysis. This study was conducted using SciVerse Scopus which has been used in several previously published bibliometric studies [ 30 37 ]. The choice of Scopus was based on the advantages it has over Web of Science and Pubmed [ 38 ].…”
Section: Methodsmentioning
confidence: 99%